Diagnosing deep vein thrombosis in cancer patients with suspected symptoms: An individual participant data meta‐analysis. (8th July 2020) - Takada, Toshihiko; van Doorn, Sander; Parpia, Sameer; de Wit, Kerstin; Anderson, David R.; Stevens, Scott M.; Woller, Scott C.; ten Cate‐Hoek, Arina J.; Elf, Johan L.; Kraaijenhagen, Roderik A.; Schutgens, Roger E. G.; Wells, Phil S.; et al.
Abstract: Background: A previous individual participant data (IPD) meta‐analysis showed that the Wells rule and D‐dimer testing cannot exclude suspected deep vein thrombosis (DVT) in cancer patients. Objectives: To explore reasons for this reduced diagnostic accuracy and to optimize the diagnostic pathway for cancer patients suspected of DVT. Patients and Methods: Using IPD from 13 studies in patients with suspected DVT, DVT prevalence and the predictive value of the Wells rule items and D‐dimer testing were compared between patients with and without cancer. Next, we developed a prediction model with five variables selected from all available diagnostic predictors. Results: Among the 10 002 suspected DVT patients, there were 834 patients with cancer. The median prevalence of DVT in these patients with cancer was 37.5% (interquartile range [IQR], 30.8‐45.5), whereas it was 15.1% (IQR, 11.5‐16.7) in patients without cancer. Diagnostic performance of individual Wells rule items and D‐dimer testing was similar across patients with and without cancer, except "immobility" and "history of DVT." The newly developed rule showed a pooled c‐statistic 0.80 (95% confidence interval [CI], 0.75‐0.83) and good calibration. However, using this model, still only 4.3% (95% CI, 3.0‐5.7) of the suspected patients with cancer could be identified with a predicted DVT posttest probability of <2%. Conclusions: Likely because of the high prevalence of DVT, clinical models followed by D‐dimer testing fail to rule out DVT efficiently in cancer patients suspected of DVT. Direct referral for compression ultrasonography appears to be the preferred approach for diagnosis of suspected DVT in cancer patients.